Conceptualizing mass violence : representations, recollections, and reinterpretations - Aafreedi, Navras Jaat HerausgeberIn; Singh, Priya HerausgeberIn (Mass violence in modern history, 2021)
"Conceptualizing Mass Violence draws attention to the conspicuous inability to inhibit mass violence in myriads forms and considers the plausible reasons for doing so. Focusing on a postcolonial perspective, the volume seeks to popularize and institutionalize the study of mass violence in South Asia. The volume is essential reading for postgraduate students and scholars from the interdisciplinary fields of Holocaust and Genocide Studies, History, Political Science, Sociology, World History, Human Rights, and Global Studies"--